1985
DOI: 10.1159/000183479
|View full text |Cite
|
Sign up to set email alerts
|

Serum Potassium Concentrations in Cyclosporine- and Azathioprine-Treated Renal Transplant Patients

Abstract: Hyperkalemia was commonly observed in successful renal transplant patients treated with cyclosporine and prednisone. At 1, 3 and 6 months after transplantation, 13 of 50, 9 of 50, and 5 of 50 patients, respectively, had serum concentrations of potassium greater than 5 mEq/1. This contrasts with the finding of hyperkalemia in only 1 of 13 comparable patients treated with azathioprine and prednisone. Mean serum concentrations of potassium at these dates were significantly higher in cyclosporine-treated patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Although cyclosporin A (CsA) has been hailed as a major advance in transplantation, increasing both graft and patient survival, its use is sometimes limited by nephrotoxicity and hyperkalemia which have been commonly observed in renal transplant patients successfully treated with cyclosporine (1,2). The pathogenesis of CsA-induced nephrotoxicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cyclosporin A (CsA) has been hailed as a major advance in transplantation, increasing both graft and patient survival, its use is sometimes limited by nephrotoxicity and hyperkalemia which have been commonly observed in renal transplant patients successfully treated with cyclosporine (1,2). The pathogenesis of CsA-induced nephrotoxicity remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Formerly, several reports have suggested that the development of hyperkalemia is specifically associated with the therapeutic administration of CsA, and it was believed that the mechanism of hyperkalemia involved the reduction of potassium secretion as a result of renal tubular damage and hypoaldosteronism (2,5). But recently, Suzuki et al (6) reported that prolonged use of CsA suppresses DNA and RNA synthesis, as well as Na Thyroxine administration has shown protective effects in several experimental models of acute renal failure induced by various and numerous nephrotoxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…In order to check this hypothesis, we studied the use of the drug in two clinical situations : in kidney transplantation and in patients with steroid-resistant idiopathic nephrotic syndrome. In neither of these two groups did we detect hyperkalaemia, which is considered as one of the sideeffects of the drug [26,27]. Although a high level of blood potassium was found in the transplant patients before surgery, it decreased to normokalaemia immediately after transplantation.…”
Section: Discussionmentioning
confidence: 65%
“…An early description of these effects was published in 1983 when seven out of 43 patients treated with cyclosporine (CsA) treated developed hyperkalemia and hyperchloremic metabolic acidosis despite a preserved glomerular filtration rate (1). Subsequently, other studies have reported an incidence of CNI-associated hyperkalemia and hypertension that ranges between 10% and 33% (2)(3)(4), and which appears to be higher with tacrolimus.…”
Section: Case Discussionmentioning
confidence: 95%